Regeneration of human-ear-shaped cartilage with acellular cartilage matrix-based biomimetic scaffolds. (September 2020) - Jia, Litao; Zhang, Ying; Yao, Lin; Zhang, Peiling; Ci, Zheng; Zhang, Wei; Miao, Chunlei; Liang, Xiaoqin; He, Aijuan; Liu, Yu; Tang, Shengjian; Zhang, Ruhong; et al.
Abstract: Tissue engineering technology provides a promising approach for external ear reconstruction. Although the first clinical breakthrough of tissue engineered auricular reconstruction has been achieved based on polymer scaffold, the discrepant clinical efficacy among different patients triggered by residual scaffold mediated aseptic inflammatory reaction seriously hinders its further clinical application. A proper natural scaffold with low inflammatory reaction is urgently required to address this problem. Among all the natural materials, acellular cartilage matrix (ACM) is considered to be the ideal cartilage-specific microenvironmental biomimetic scaffold. However, no breakthroughs have been achieved for the regeneration of human-ear-shaped cartilage based on ACM so far. The main challenge is how to prepare ACM into a three-dimensional (3D) porous scaffold with precise human-ear shape and proper mechanical strength. In this study, ACM powder, prepared by freezing pulverization and decellularization, was successfully prepared into 3D porous scaffolds using gelatin as an auxiliary crosslinker. By optimizing proportion and concentration of ACM and gelatin, the scaffolds presented proper pore structure and degradation rate as well as good mechanical strength and biocompatibility. Furthermore, ACM/Gelatin could be fabricated into porous scaffolds with precise human-ear shape and proper mechanical strength by integrating 3D printing, polycaprolactone (PCL) inner core designing, cast molding, and freeze-drying technologies. Finally, human-ear-shaped cartilage with good elasticity and cartilage-specific extracellular matrices was successfully regenerated using the ACM/Gelatin-PCL scaffolds and auricular chondrocytes (elastic cartilage). All of these results provide important support for the application and clinical translation of human-ear-shaped cartilage. Graphical abstract: Image, graphical abstract